Penyelesaian Sengketa Tanah Dengan Mediasi Oleh Kementerian Agraria Tata Ruang/Badan Pertanahan Nasional Kota Kupang - Bahy Frederick J Eryansan; Samuel J Boesday; Benediktus Petter Lay; Vinsensius Samara (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Â This research aims to analyze the settlement of land disputes through non-litigation channels, especially mediation at the Kupang City Office of the Ministry of ATR/BPN. This research focuses on the mediation mechanism in the settlement of land disputes at the Kupang City Office of the Ministry of ATR / BPN, and what factors are an obstacle in the mediation of land disputes carried out. The research is descriptive with empirical juridical type. The research revealed that land disputes filed with the Kupang City BPN must be registered or certified land. The settlement of land disputes through mediation in the Kupang City Office of the Ministry of ATR / BPN is guided by the Regulation of the Minister of ATR / BPN No.21 of 2020 in which the handling of land disputes through mediation starts from a complaint, case assessment, initial degree, research, exposing research results, coordination meeting, final degree, and case settlement. The inhibiting factor in mediation caused by the complaint document does not yet contain the stipulated conditions that must be met first, the supporting data factor, the absence of one of the parties, the factor of one party's dissatisfaction with the agreed peaceÂ